Comparative Bioavailability of Propafenone after Administration of a Magistral Suspension vs. Commercial Tablets in Healthy Volunteers - Juárez Olguín, Hugo; Flores Pérez, Carmen; Ramírez Mendiola, Bianca; Barranco Garduño, Lina; Sandoval Ramírez, Eunice; Flores Pérez, Janett (Arzneimittelforschung, 2009)
Propafenone (CAS 34183-22-7) is an effective antiarrhythmic drug used in children, although in some countries no specific pediatric formulation is available. The aim of this study is to compare the relative bioavailability of a magistral (MAG) preparation of propafenone versus its commercial (COM) presentation in a group of 16 Mexican healthy volunteers. Bioavailability was determined after crossover administration of the drugs, through a randomized two-phase trial. All volunteers had normal hepatic and renal functions, determined clinically at the beginning of the study, and received 150 mg of either COM (tablets) or MAG (suspension). Blood samples were drawn for a 24-h post-dose analysis by HPLC to measure plasma levels of propafenone. Subjects (mean 25.9 ± 5.3 years and 66.1 ± 12.4 kg) had the following pharmacokinetic parameters: Cmax 189.9 ± 20.92 ng/mL, Tmax 1.5 h, AUC 322.4 ± 36.28 ng • ml1 • h for COM. Values for MAG were Cmax 225.8 ± 24.38 ng/mL, Tmax 1.7 h and AUC 359.3 ± 27.90 ng • ml1 • h. These values yielded a relative bioavailability of 111.42 % for MAG compared with COM. No electrocardiographic changes were recorded in any subject with respect to the baseline value, in both treatment schemes. Therefore, propafenone suspension prepared as a magistral formulation may be used as an alternative drug in pediatric patients.
Keywords: Antiarrhythmics; CAS 34183-22-7; Propafenone, bioavailability, healthy volunteers, hospital pharmacy, pharmacokinetics